Literature Review of Permanent Magnet AC Motors and Drive for Automotive Application - Rakesh Ghanshyamlal Shriwastava; M.B. Diagavane; S.R. Vaishnav (Institute of Advanced Engineering and Science, 2012)
Permanent Magnet Synchronous Motor (PMSM’s) are used in many applications that require rapid torque response and high – performance operation. New developed materials such as magnetic materials, conducting materials and insulating materials as well as several new applications have greatly contributed to development of small and special purpose machines. Using such materials the size of the motor would considerably reduce and high performance motors can be built. Due to several new applications these motors are quite popular &use in a developing country such as India for Automotive application. In a permanent magnet synchronous motor, the dc field winding of the rotor is replaced by a permanent magnet. The advantages are elimination of field copper loss, higher power density, lower rotor inertia and more robust construction of the rotor. The demerits are loss of flexibility of field flux control and possible demagnetization effect. The PMSM has higher efficiency than an induction motor, but generally its cost is higher, which makes the life cycle cost of the drive somewhat lower. PMSM particularly at low power range are widely used in industry. Recently, the interest in their application is growing, particularly up to 100 KW, only reluctance motor are simpler in construction and in assembly procedure then PMSM, but reluctance motor generally developed less torque per unit of current and per unit of weight. Therefore, on a basis of power output per unit weight (and general, per unit volume) the PMSM is superior to all other brushless synchronous motor especially with the commercial feasibility of rare earth magnets. Section 1. describes the introduction section 2.describes Classification of permanent magnet AC motor section 3. describes the conclusion.